Volume 1: Development and Characterization of Multifunctional Materials; Modeling, Simulation and Control of Adaptive Systems; 2012
DOI: 10.1115/smasis2012-8023
|View full text |Cite
|
Sign up to set email alerts
|

Optical Fibre Sensing of High Order Lamb Waves for Structural Health Monitoring

Abstract: Lamb waves provide arguably the best prospect for achieving a structural health monitoring (SHM) capability with broad diagnostic coverage at sensor densities that are not impractically high. The traditional approach in Lamb wave SHM is to employ a single mode, typically one of the fundamental modes, in a non-dispersive and easily excited regime, which is done largely to simplify the interpretation of the elastic wave dynamics. However, the diagnostic value of an interrogation conducted using only the fundamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…When interrogated using intensity-based methods [7] they are capable of detecting high frequency wave-fields with the bandwidth limited only by the photo-current to voltage conversion electronics (typically > 100 MHz). Recent work by the authors has demonstrated the ability of FBGs to measure strain-fields at frequencies in excess of 2 MHz [1].…”
Section: Introductionmentioning
confidence: 99%
“…When interrogated using intensity-based methods [7] they are capable of detecting high frequency wave-fields with the bandwidth limited only by the photo-current to voltage conversion electronics (typically > 100 MHz). Recent work by the authors has demonstrated the ability of FBGs to measure strain-fields at frequencies in excess of 2 MHz [1].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work was constrained to a relatively low frequency regime (≤ 200kHz) because of a limitation related to the ratio of the sensor length to the acoustic wavelength [12]. Recent experimental work has demonstrated a significant increase in the plate-wave frequency bandwidth of an in-situ FBG, which has been shown to resolve the elastic wave dynamics in a metallic plate at frequencies of up to 2 MHz [13].…”
Section: Dsto Technical Program Overviewmentioning
confidence: 99%
“…Optical fiber sensors are not only more durable than piezo-ceramic sensors but are also immune to electromagnetic interference, have a small footprint which allows them to be easily embedded in fiber composites, and in the case of FBGs are readily multiplexed allowing for distributed sensing. Recent studies have shown that FBG sensors can achieve high bandwidths and are thus capable of detecting higher order Lamb waves [ 6 ] and when written in a high-density array are capable of resolving multi-modal wave packets into constituent modes [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%